Separation of low polarity petroleum sulfonate: Eluant selection, characterization, and theoretical calculation. Issue 1 (2nd January 2019) - Liu, Xintong; Xue, Yanan; Zhu, Youyi; Fan, Jian; Liu, Shixiang; Li, Hongda; Zhao, Yanjun; Li, Wenjun
ABSTRACT: Petroleum sulfonate is one of the most important surfactant in tertiary oil recovery process. Among complex components, low polarity petroleum sulfonate account for about 70% of total, but the main contributing components are still unknown, and the accurate evaluation method is imperative. In this work, low polarity petroleum sulfonate was successfully separated into four parts. All the separated samples were characterized by mass spectrometry, infrared spectroscopy, and nuclear magnetic resonance. The average carbon number, average aromatic carbon number, average saturated carbon number, and the average number of methyl were obtained. The results revealed that average relative molecular mass and branched degree are the main factors of varied polarities of petroleum sulfonate. What more, this study provided a reliable evaluation and characterization method of low polarity petroleum sulfonate.